Exploring the Synergy Between Artificial Intelligence and Human Resources: A Qualitative Review of Business Management Literature - Girlovan Aura; Horobet Alexandra; Botoroga Cosmin-Alin; Belascu Lucian; Lucian Paul (Studies in Business and Economics)
This paper portrays the role of the interplay between artificial intelligence and human resources as evidenced by an extensive review of academic literature. The study investigated 402 abstracts of scholarly articles published in the Business Management and Accounting domain of the Scopus database spanning from 2000 to 2023. Using QDA Miner 2024, a novel approach based on content, link, and proximity analysis was employed to conduct the literature review. Three major findings were revealed by our investigation. First, while codes such as ‘AI’ and ‘employees’ dominate the academic discourse, there is an evolving trend toward more sophisticated analyses of AI-human resources interactions, including their impact on business strategies and performance. Second, research methods show significant diversification over time, going from more descriptive approaches to sophisticated quantitative and qualitative methodologies. Third, several areas appear to lack research focus, such as the connection between employee recruitment and future career paths with AI and business progress. The findings contribute to understanding how the technological revolution shapes business operations, particularly workforce management, while highlighting the need for structural reforms in organizational approaches to AI adoption, and provide valuable insights for both scholars and practitioners interested in the integration of AI in human resource management.